HIV Testing as a Standard of Care for Men Who Have Sex With Men - Jill Owczarzak PhD; Julia Lechuga PhD; Andrew Petroll MD (Journal of Primary Care & Community Health, 2011)
In 2006, the Centers for Disease Control and Prevention (CDC) revised its HIV testing recommendations in health care settings. Current guidelines recommend that all patients aged 13 to 64 years be screened for HIV as part of routine medical care. Additionally, the CDC recommends that persons at high risk for HIV infection should be screened for HIV at least annually. Primary care providers in clinical settings are seen as important providers of HIV prevention services and will be critical to expand HIV testing rates, particularly among populations such as men who have sex with men (MSM). This article reports on results from a multifaceted study that combined qualitative and quantitative methods and targeted both MSM and primary care providers. Through a quantitative survey with 709 MSM in Wisconsin, we explored the relationship between having a primary care provider, risk behavior, and HIV testing patterns. In the qualitative portion of the study, we conducted structured interviews with 7 clinic medical directors to explore the acceptability and feasibility of increased HIV testing in clinical setting strategy among primary care providers. Consistent with previous research, the results of this study indicate that primary care providers can play a significant role in encouraging and facilitating annual routine testing as a standard of care for high-risk MSM. This article offers policy and practice recommendations based on these findings.